2015
DOI: 10.1007/s11150-015-9316-7
|View full text |Cite
|
Sign up to set email alerts
|

Emancipation under the great recession in Spain

Abstract: In this paper we document the behavior of emancipation over one of the biggest boom-bust cycles experienced by the Spanish economy. In principle, the economic difficulties faced by the Spanish youth during the last recession would have hampered a normal emancipation pace. However, we find that the proportion living away from parents among those aged 18-40 has not decreased but increased from 44 % during the boom (2005)(2006)(2007)(2008) to 46 % during the bust (2009)(2010)(2011)(2012)(2013). A simple decomposi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 15 publications
1
19
0
2
Order By: Relevance
“…This explanation is supported by the fact that in the Nordic countries the disadvantage is attenuated and loses significance when financial deprivation is controlled for, while there is no to little change in the Familialistic and TPS countries. Further support comes from a study by Ahn and Sánchez-Marcos (2015), who found that in Spain the proportion living alone increased during the financial crises (2009)(2010)(2011)(2012)(2013)) as compared to the boom years before, and that this rise was mainly driven by the full-time employed.…”
Section: Discussionmentioning
confidence: 99%
“…This explanation is supported by the fact that in the Nordic countries the disadvantage is attenuated and loses significance when financial deprivation is controlled for, while there is no to little change in the Familialistic and TPS countries. Further support comes from a study by Ahn and Sánchez-Marcos (2015), who found that in Spain the proportion living alone increased during the financial crises (2009)(2010)(2011)(2012)(2013)) as compared to the boom years before, and that this rise was mainly driven by the full-time employed.…”
Section: Discussionmentioning
confidence: 99%
“…Por último, y a pesar de que Portugal no sufrió una burbuja inmobiliaria cuyo estallido hubiera contribuido a agravar la situación económica general (Correia et al, 2014), es preciso igualmente tener en cuenta cuál fue la evolución del mercado inmobiliario, dado que, en el modelo mediterráneo, la formación de nuevos hogares se produce habitualmente por la vía de la propiedad (Ahn y Sánchez-Marcos, 2017;Giannelli y Monfardini, 2003;Lee y Painter, 2013).…”
Section: Creación De Nuevos Hogares Y Condiciones Económicas En Portugal (2003-2017)unclassified
“…In the United States, 80 percent of men have left by the age of 29; in Italy that percentage decreases 59 percent. 2 The largest gap between the two countries is observed in the age class 25-29 (42 pp.). Even at older age classes, the gap remains large and it does not close completely.…”
Section: Datamentioning
confidence: 99%
“…More recently, Billari and Tabellini (2010) explore to what extent the late transition to adulthood contributed to the disappointing performance of the Italian economy of recent years. Taking the opposite point of view, Ahn and Sánchez-Marcos (2017) focus, instead, on the effect of the Spanish recession of 2009-2013 on the emancipation rate of young adults. Several researchers have looked at the role of cultural differences and social norms.…”
Section: Introductionmentioning
confidence: 99%